Influência das formas de uso e ocupação da terra no ecossistema áquatico da bacia hidrográfica do arroio Cadena em Santa Maria - RS - Reis, Janete Teresinha (2006)
The study had as objective relates the forms of the land uses with the aquatic ecosystem of the Cadena's stream catchment, identifying its critical points about the environmental conditions. The methodological proposal, accomplished in stages, it made possible to analyze the aquatic and terrestrial systems, as well as its influence on that, and the forms of the land uses influenced in the aquatic system, altering the original characteristics of the water. The point 1 located in the portion amount was characterized by the high index of urbanized area and absence of forests, breaking the natural balance of the aquatic ecosystem. The circumstances presented by the analyzed limnological and bacteriological variables allow inferring that this point presents the largest index of contamination. As well as, the point 3 located in the proximities on Sete de Setembro Street and the point 5 located close to Borges de Medeiros Avenue that also present high tenor of contamination. In compensation, the point 4 located in the Chácara das Flores, it stands out for the forest index in it influence area, above 60% and the smallest index of the water contamination. The accomplished analyses demonstrated small alteration; however it can be classified inside of the original patterns. In a general way, the aquatic ecosystem of the Cadena's stream is committed, because of the inadequate forms of the land uses. This way, it was identified the points 1, 3 and 5 like the most critics, whose water presented significant alterations as to the physical, chemistries and bacteriological properties, presenting high contamination. However, the Cadena s stream catchment shouts for its ecosystem recovering, which must leave from the beginning in the land use form and occupation